Identification and characterization of outcome measures reported in animal models of epilepsy: Protocol for a systematic review of the literature–A TASK2 report of the AES/ILAE Translational Task Force of the ILAE. (6th November 2017) - Simonato, Michele; Iyengar, Sloka; Brooks‐Kayal, Amy; Collins, Stephen; Depaulis, Antoine; Howells, David W.; Jensen, Frances; Liao, Jing; Macleod, Malcolm R.; Patel, Manisha; Potschka, Heidrun; Walker, Matthew; et al.
Summary: Current antiseizure therapy is ineffective in approximately one third of people with epilepsy and is often associated with substantial side effects. In addition, most current therapeutic paradigms offer treatment, but not cure, and no therapies are able to modify the underlying disease, that is, can prevent or halt the process of epileptogenesis or alleviate the cognitive and psychiatric comorbidities. Preclinical research in the field of epilepsy has been extensive, but unfortunately, not all the animal models being used have been validated for their predictive value. The overall goal of TASK2 of the AES/ILAE Translational Task Force is to organize and coordinate systematic reviews on selected topics regarding animal research in epilepsy. Herein we describe our strategy. In the first part of the paper we provide an overview of the usefulness of systematic reviews and meta‐analysis for preclinical research and explain the essentials for their conduct. Then we describe in detail the protocol for a first systematic review, which will focus on the identification and characterization of outcome measures reported in animal models of epilepsy. The specific goals of this study are to define systematically the phenotypic characteristics of the most commonly used animal models, and to effectively compare these with the manifestations of human epilepsy. This will provide epilepsy researchers with detailed information on the strengths and weaknesses of epilepsy models, facilitating their refinement and future research. Ultimately, this could lead to a refined use of relevant models for understanding the mechanism(s) of the epilepsies and developing novel therapies.